A critical companion to English Mappae mundi of the twelfth and thirteenth centuries - Terkla, Dan; Millea, Nick (Boydell studies in medieval art and architecture., 2019)
"Mappae mundi (maps of the world), beautiful objects in themselves, offer huge insights into how medieval scholars conceived the world and their place within it. They are a fusion of "real" geographical locations with fantasical, geographic, historical, legendary and theological material. Their production reached its height in England in the twelfth and thirteenth centuries, with such well-known examples as the Hereford map, the maps of Matthew Paris, and the Vercelli map. This volume provides a comprehensive Companion to the seven most significant English mappae mundi. It begins with a survey of the maps' materials, types, shapes, sources, contents, conventions, idiosyncrasies, commissioners and users, moving on to locate the maps' creation and use in the realms of medieval rhetoric, Victorine memory theory and clerical pedagogy. It also establishes the shared history of map and book making, and demonstrates how pre-and post-Conquest monastic libraries in Britain fostered and fed their complementary relationship. A chapter is then devoted to each individual map. An annotated bibliography of multilingual resources completes the volume."